2003
DOI: 10.1037/1040-3590.15.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Interchangeability of the Working Alliance Inventory and Working Alliance Inventory, Short Form.

Abstract: Working Alliance Inventory (WAI) ratings were compared with ratings comprising the 12-item WAI, Short Form (WAI-S). Responses were collected from 54 university counseling center client-therapist pairs after the 4th therapy session as well as at a final ratings point. WAI and WAI-S scores were highly correlated and had comparable descriptive statistics, internal consistencies, and subscale intercorrelations within and across rater perspectives. Predictive validity estimates for WAI and WAI-S total scales were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
203
6
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(225 citation statements)
references
References 16 publications
14
203
6
2
Order By: Relevance
“…Contrary to the overall sample, and what is common in the literature, the therapist rated the working alliance higher across sessions (m = 4.89) than Cora (m = 4.35). In the final session the client rated the alliance 4.83, which is more than one standard deviation below what is reported to be a general level in out-patient samples (final session WAI-S: 5.96, sd = .80), while the therapist's rating (5.58) was in line with general findings (5.50, sd = .88; Busseri & Tyler, 2003).…”
Section: The Quantitative Resultssupporting
confidence: 56%
“…Contrary to the overall sample, and what is common in the literature, the therapist rated the working alliance higher across sessions (m = 4.89) than Cora (m = 4.35). In the final session the client rated the alliance 4.83, which is more than one standard deviation below what is reported to be a general level in out-patient samples (final session WAI-S: 5.96, sd = .80), while the therapist's rating (5.58) was in line with general findings (5.50, sd = .88; Busseri & Tyler, 2003).…”
Section: The Quantitative Resultssupporting
confidence: 56%
“…The scores from the short 12-item version used in this study have been found to reflect those of the longer 36-item form (Busseri & Tyler, 2003). Reliability estimates (ïĄ) of the WAI range from 0.84-0.93 (Fenton, Cecero, Nich, Frankforter, & Carroll, 2001).…”
Section: Working Alliance Inventory (Wai)mentioning
confidence: 82%
“…Working alliance was assessed using the Working Alliance Inventory Short Form (WAI-S) Client Version. The scale has shown to be acceptable with a SMI population (Busseri & Tyler, 2003;Gehrs & Goering, 1994;Horvath & Greenberg, 1989;Tracey & Kokotovic, 1989). The measure has demonstrated good reliability and validity (Horvath & Greenberg, 1989;Tracey & Kokotovic, 1989).…”
Section: Methodsmentioning
confidence: 92%
“…The measure has demonstrated good reliability and validity (Horvath & Greenberg, 1989;Tracey & Kokotovic, 1989). We used the 12-item version (Tracey & Kokotovic, 1989), which has also demonstrated reliability and validity (Busseri & Tyler, 2003;Gehrs & Goering, 1994;Tracey & Kokotovic, 1989). In our sample, internal consistency was good (α = 0.84).…”
Section: Methodsmentioning
confidence: 99%